Measurements of the sediment flocculation characteristics in the Three Gorges Reservoir, Yangtze River. (3rd March 2020) - Li, Wenjie; Yu, Chengfeng; Yang, Shengfa; Yang, Yunping; Yang, Wei; Xiao, Yi
Abstract: The flocculation of fine sediments in the Three Gorges Reservoir (TGR) was confirmed in previous studies, but the flocculation characteristics have yet to be fully clarified. In this study, field measurements were conducted in the TGR to investigate the sediment flocculation characteristics. First, the instantaneous flow velocity and sediment concentration were measured through Acoustic Doppler velocimeter and sediment sampling. Then, the effective settling velocity was calculated based on the sediment diffusion theory to deduce the floc size and flocculation degree. Finally, the influences of particle size, flow velocity, and sediment concentration on flocculation were analyzed. Results showed that flocculation occurred in more than half of the sediments in the TGR, and the maximum flocculation degree was between 10 and 30. Flocculation weakened as particle diameter increased, with the critical particle size being approximately 0.018 mm, meaning that flocculation was unlikely to occur when the particle size exceeded the critical value. As the flow velocity increased, the flocculation degree first increased and then decreased, with the critical flow velocity being approximately 0.7 m/s, but the critical flow velocity increased with an increase in sediment concentration and tended to be a constant. The flocculation degree also increased with increasing sediment concentration and tended to be constant when the sediment concentration exceeded approximately 0.5 kg/m 3 . The results provide new information on the flocculation characteristics of the TGR and should be useful for understanding and simulating fine sediment transport in the TGR.